The THE RELATIONSHIP BETWEEN ORGANIZATIONAL CLIMATE FOR INNOVATION AND INNOVATIVE WORK BEHAVIOR: MEDIATING ROLE OF EMPLOYEE ENGAGEMENT IN PAKISTAN (Malaysian Management Journal, 2020)
The purpose of this study is to empirically investigate the mediating result of employee engagement between organisational climate for innovation and innovative work behaviour. This study will have positive contribution towards theory. The tool used for data collection was closed-ended questionnaire. Results indicated that organisational climate for innovation and innovative work behaviour has a direct and indirect impact on innovative work behaviours. In this study, employee engagement has partial mediation impact between the organisational climate for innovation and innovative work behaviour. Approximately, 210 respondents participated in this study. The unit of analysis used in this study was employees. For practical implication, it will be useful for HR specialists who are concerned in increasing successful intercession that encourage employees to engage in innovative work behaviour. This paper offers contribution to the understanding of the relationship between the innovative work behaviour and organisational climate and mediating role of employee engagement.